Local activation of focal adhesion kinase orchestrates the positioning of presynaptic scaffold proteins and Ca2+ signalling to control glucose-dependent insulin secretion - Jevon, Dillon; Deng, Kylie; Hallahan, Nicole; Kumar, Krish; Tong, Jason; Gan, Wan Jun; Tran, Clara; Bilek, Marcela; Thorn, Peter (eLife, 2022)
A developing understanding suggests that spatial compartmentalisation in pancreatic β cells is critical in controlling insulin secretion. To investigate the mechanisms, we have developed live-cell subcellular imaging methods using the mouse organotypic pancreatic slice. We demonstrate that the organotypic pancreatic slice, when compared with isolated islets, preserves intact β-cell structure, and enhances glucose-dependent Ca2+ responses and insulin secretion. Using the slice technique, we have discovered the essential role of local activation of integrins and the downstream component, focal adhesion kinase (FAK), in regulating β cells. Integrins and FAK are exclusively activated at the β-cell capillary interface and using in situ and in vitro models we show their activation both positions presynaptic scaffold proteins, like ELKS and liprin, and regulates glucose-dependent Ca2+ responses and insulin secretion. We conclude that FAK orchestrates the final steps of glucose-dependent insulin secretion within the restricted domain where β-cell contact the islet capillaries.
Keywords: exocytosis; secretion; calcium